Three-Dimensional Printing of an Apigenin-Loaded Mucoadhesive Film for Tailored Therapy to Oral Leukoplakia and the Chemopreventive Effect on a Rat Model of Oral Carcinogenesis - Hiroyuki Takashima; Tatsuaki Tagami; Shinichiro Kato; Heeju Pae; Tetsuya Ozeki; Yasuyuki Shibuya (MDPI AG, 2022)
Oral leukoplakia, which presents as white lesions in the oral cavity, including on the tongue, is precancerous in nature. Conservative treatment is preferable, since surgical removal can markedly reduce the patient's quality of life. In the present study, we focused on the flavonoid apigenin as a potential compound for preventing carcinogenesis, and an apigenin-loaded mucoadhesive oral film was prepared using a three-dimensional (3D) bioprinter (semi-solid extrusion-type 3D printer). Apigenin-loaded printer inks are composed of pharmaceutical excipients (HPMC, CARBOPOL, and Poloxamer), water, and ethanol to dissolve apigenin, and the appropriate viscosity of printer ink after adjusting the ratios allowed for the successful 3D printing of the film. After drying the 3D-printed object, the resulting film was characterized. The chemopreventive effect of the apigenin-loaded film was evaluated using an experimental rat model that had been exposed to 4-nitroquinoline 1-oxide (4NQO) to induce oral carcinogenesis. Treatment with the apigenin-loaded film showed a remarkable chemopreventive effect based on an analysis of the specimen by immunohistostaining. These results suggest that the apigenin-loaded mucoadhesive film may help prevent carcinogenesis. This successful preparation of apigenin-loaded films by a 3D printer provides useful information for automatically fabricating other tailored films (with individual doses and shapes) for patients with oral leukoplakia in a future clinical setting.